2018
DOI: 10.12669/pjms.344.15654
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcome among fasting and non fasting mothers during the month of Ramadan

Abstract: Objective:To compare the perinatal outcome among fasting and non fasting pregnant mothers.Methods:A total of 180 women, who came for delivery in the labor suite were included, after verbal informed consent. These women were divided in two groups fasting (n=100), and non-fasting (n=80).Results:The mean age of the mothers was 27.16±4.27 years in the fasting group and 27.36±4.92 years in non-fasting group. The average BMI of mothers was 25.31±3.26 kg/m2in fasting group while 25.64±3.58 kg/m2in non-fasting group. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 12 publications
0
10
1
Order By: Relevance
“…These findings were pretty similar to what was found in another local study where mean age of the fasting and non-fasting group were 27.16±4.27 and 27.36±4.92 years respectively. 15 No difference in demographical characteristics of both study groups observed noted in the present study except significantly less women in the fasting group were employed. Our findings were consistent with those of Safari K et al from Iraq 10 where the researchers noted only 11.0% of the women to be working women in the fasting group in comparison to 20.8% in the non-fasting group and the difference was found statistically significant.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…These findings were pretty similar to what was found in another local study where mean age of the fasting and non-fasting group were 27.16±4.27 and 27.36±4.92 years respectively. 15 No difference in demographical characteristics of both study groups observed noted in the present study except significantly less women in the fasting group were employed. Our findings were consistent with those of Safari K et al from Iraq 10 where the researchers noted only 11.0% of the women to be working women in the fasting group in comparison to 20.8% in the non-fasting group and the difference was found statistically significant.…”
Section: Discussioncontrasting
confidence: 47%
“…Similar observations are reported by other researchers as well. 15 It is advisable that pregnant ladies who wish to fast should consult a healthcare professional before the start of Ramadan. They need to be advised to have sufficient caloric and fluid intake before and after the fasting period.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the authors found positive effects on stature for exposed less-religious Muslim children that peak in early adolescence (10-14 years of age) and negative effects on stature for exposed non-Muslim children that occur only in early childhood (0-4 years of age). Pradella and van Ewijk [37] compared wheezing occurrence among adult Muslims who were exposed to RF as fetuses with those who did not. Wheezing prevalence was higher among adult Muslims who had been in utero during Ramadan, independent of the pregnancy phase in which the exposure to Ramadan occurred.…”
Section: Epidemiological Studiesmentioning
confidence: 99%
“… 17 This was also in line with our previous research on maternal fasting and perinatal outcome. 8 We did not find any changes in the hematological parameters of women before and after the fasting month. This also helps in counseling women when they complain about weakness and fatigue following fasting month.…”
Section: Discussionmentioning
confidence: 49%
“…Our group has previously reported upon the perinatal outcome among fasting and non-fasting women. 8 The results showed that fasting during pregnancy did affect birth weight, especially in boys, and also affected the placental weight at the time of delivery.…”
Section: Introductionmentioning
confidence: 96%